The Application of Collaborative Writing Strategy in Teaching Composition in a Public Junior High School - Suparto, Windy Puspitasari; Yusmah, Yusmah; Kasman, Nuraini; Amir, Muhammad; Wafi, Abdul (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The qualitative descriptive method was used by the researcher in this study. The term